“Contenido de vitamina C, polifenoles y flavonoides totales en cascarilla de dos variedades de cacao (theobroma cacao L.): nacional y CCN-51”. - Loor Intriago, Melissa Leonor (2020)
In the cocoa benefit chain (Theobroma cacao L.), 10% of the cocoa fruit is used by the chocolate industry and 90% of the components (cob, husk, mucilage) are deposited on the ground, causing losses and pollution to the environment. Cocoa husk is a residue that could have a high content of phenolic compounds, with excellent potential for use as an important source of low-cost natural antioxidants. For this reason, the objective of this research work was to evaluate the content of vitamin C, polyphenols and total flavonoids in cocoa husks of two varieties Nacional and CCN-51. The analytical determinations of the phenolic content were made by UV-VIS spectrophotometry and the vitamin C content was evaluated by HPLC chromatography, using an ion exclusion column. According to the results obtained, the national variety cocoa husk presented the lowest content of total polyphenols (29.437 mg AGE•100g -1 ) and total flavonoids (15.08 g EC • 100g -1 ); in comparison with CCN- 51 cocoa (PT: 42.17 mg AGE•100g -1 y FT: 20.57 mg CAT•100g -1 ). However, the presence of vitamin C was not identified in the two varieties studied. Through a Pearson correlation analysis, it was established that there is a strong positive correlation (0.8> r <1) between polyphenol content and antioxidant capacity (CA) measured by ABTS methods (0.9962) ; FRAP (0.8484) and ORAC (0.8484). The total flavonoid content presented a moderate positive correlation (0.5> r <0.8) with the AC measured by FRAP (0.7944) and ORAC (0.7944). y strong (0.8> r <1); while, the ABTS measured CA presented a strong positive correlation (0.8> r <1) with the flavonoid content. Therefore, the recovery of residues from the cocoa profit chain can give rise to an economical product, with a potential source of phytonutrients whose biological functions are: inhibiting pro-oxidant metal compounds, trapping | free radicals (RL) and peroxide radicals, whose reactive oxygen species (ROS) are responsible for the damage of proteins, DNA, RNA, in our body.